News-based Sentiment Indicators - Huang, Chengyu (IMF Working Papers; Working Paper, 2019)
We construct sentiment indices for 20 countries from 1980 to 2019. Relying on computational text analysis, we capture specific language like 'fear', 'risk', 'hedging', 'opinion', and, 'crisis', as well as 'positive' and 'negative' sentiments, in news articles from the Financial Times. We assess the performance of our sentiment indices as 'news-based' early warning indicators (EWIs) for financial crises. We find that sentiment indices spike and/or trend up ahead of financial crises.